Form and foreskin : medieval narratives of circumcision - Strouse, A. W. (Fordham University Press, 2021)
"Why did Saint Augustine ask God to "circumcise his lips?" Why does Sir Gawain cut off the Green Knight's head on the Feast of the Circumcision? Is Chaucer's Wife of Bath actually-as an early glossator figures her-a foreskin? And why did Ezra Pound claim that he had incubated The Waste Land inside of his uncut member? In this little book, A.W. Strouse excavates a poetics of the foreskin, uncovering how Patristic theologies of circumcision came to structure medieval European literary aesthetics. Following the writings of Saint Paul, "circumcision" and "uncircumcision" become key terms for theorizing language-especially the dichotomies between the mere text and its extended exegesis, between brevity and long-windedness, between wisdom and folly. Form and Foreskin looks to three works: a peculiar story by Saint Augustine about a boy with the long foreskin; Sir Gawain and the Green Knight; and Chaucer's Wife of Bath's Tale. By examining literary scenes of cutting and stretching, Strouse exposes how patristic treatments of circumcision queerly govern medieval poetics"--